Molten salt synthesis of (Zn, Mg) TiO3 micro/nano crystals with pure hexagonal ilmenite structure - Liu, Xiangchun; Zuo, Chenguang (Journal of materials science. Materials in electronics, 2016)
The pure hexagonal phase (Zn, Mg) TiO 3 (abbreviated to ZMT) micro/nano crystals were prepared by a molten salt method. The influences of the molten salt system and the heat treatment temperature on ZMT crystalline powders phase composition and particles morphology were studied. The results show that the formation of ZMT phase takes place at about 530 °C and the hexagonal phase stability region is 530–810 °C in KCl–NaCl salt system when MgCl 2 ·6H 2 O taken in excess. Compared to the conventional solid phase process, the formation temperature of hexagonal ZMT via the molten salt method is lower. The ZMT powders prepared by the molten salt method are indicative more uniform grain size distribution and small grain size (the average grain size is about 150 nm).